Development of a method to increase the resilience of hybrid work systems (human and robot) in the context of human centricity- a contribution to Industry 5.0 - Ciftci, Muhammed Ali (Stellenbosch : Stellenbosch University, 2025)
Thesis (MEng)--Stellenbosch University, 2024.